Research Acculturation Grant Scheme (RAGS) - Ahmad Saifudin, Mohd Kamel (Penerbit UMP, 2012)
Research Acculturation Grant Scheme (RAGS) is a fund to promote research acculturation among young researchers in non-RU public institutes of higher learning (IPTAs). It will serve as a basis to build up research performance so they can be equally competitive at the national and international levels.